SYSTEMATIC LITERATURE REVIEW HUBUNGAN KONSUMSI NATRIUM DENGAN KEJADIAN HIPERTENSI PADA REMAJA - Asyifa Delfilaura; Fitrisia Amelin; Rizanda Machmud (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Background : Hypertension does not only occur in adults but also in adolescents, it will be very risky to develop into serious early disease. One of the risk factors for hypertension is the habit of consuming high amounts of sodium, especially in adult hypertension. However, the relationship between sodium intake and the incidence of hypertension in children and adolescents is still controversial and the literature review studies found are still few. Objective : This research aim to assess the relationship between sodium intake with hypertension in adolescents based on literature review. Methods : This research is a systematic literature review. A literature search was conducted on the Pubmed and Google Scholar databases using inclusion and exclusion criteria. The data synthesis in this literature review was carried out quantitatively. Results : A total of 8 studies were included in the systematic which 4 studies from them is carried out a meta-analysis. The average adolescent consumes sodium above the requirement ranging from 1503 mg per day to 4000 mg per day. The average prevalence of hypertension in adolescents is 2.2% - 35.8%. From the results of the meta-analysis, it was found that there was a significant relationship between sodium consumption and the incidence of hypertension in adolescents with a value of P = 0.00001 (P <0.05). Conclusion : Most adolescents consume sodium above the nutritional recommendation. The prevalence of adolescent hypertension continues to increase. There is a significant relationship between sodium intake and hypertension in adolescents.